Muzara’ah Dan Dampaknya Terhadap Kesejahteraan Petani Ikan Di Kecamatan Lingsar Kabupaten Lombok Barat - akhmad jufri; Sahri sahri; Moh Huzaini (ITB AAS INDONESIA Surakarta, 2023)
The study aims to analyse the implementation of muzara'ah and its impact on the welfare of freshwater fish farmers in Lingsar sub-district, West Lombok Regency, from Islamic perspectives. This study used a qualitative approach and a descriptive method. The data was collected using participatory observation methods, in-depth and documentation techniques in the form of sound recordings and pictures. Informants were determined by snowball and purposive sampling techniques. The data was analysed using an interactive model that included data reduction, display, and conclusion drawing. The study revealed that the background of muzara'ah cooperation in raising fish in Lingsar sub-district, West Lombok Regency, is based on the principle of economic mutual need and mutual help (ta'awun). Muzara'ah in fish raising was in accordance with Islamic law, namely the fulfilment of the pillars and legal conditions for the implementation of muzara'ah. Likewise, muzara'ah had an impact on the Islamic welfare of fish farmers in terms of protecting religion (al-Din), the soul (al-Nafs), the mind (al-Aql), offspring (an-nasf), and property (al-Mal).